The role of evolutionary processes in producing biodiversity patterns, and the interrelationships between taxonomic, functional and phylogenetic biodiversity - Swenson, Nathan G. (American journal of botany, 2011)
Patterns of biodiversity are ultimately the product of speciation and extinction. Speciation serves as the biodiversity pump while extinction serves as the agent that culls global to local levels of biodiversity. Linking these central processes to global and local patterns of biodiversity is a key challenge in both ecology and evolution. This challenge necessarily requires a simultaneous consideration of the species, phylogenetic, and functional diversity across space and the tree of life. In this review, I outline a research framework for biodiversity science that considers the evolutionary and ecological processes that generate and cull levels of biodiversity and that influence the inter-relationships between species, phylogenetic, and functional diversity. I argue that a biodiversity synthesis must begin with a consideration of the inherently ecological process of speciation and end with how global biodiversity is filtered into local-scale plant communities. The review ends with a brief outlook on future challenges for those studying biodiversity, including outstanding hypotheses that need testing and key data limitations.